2022
DOI: 10.2196/33329
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes Through Personalized Recommendations in a Remote Diabetes Monitoring Program: Observational Study

Abstract: Background Diabetes management is complex, and program personalization has been identified to enhance engagement and clinical outcomes in diabetes management programs. However, 50% of individuals living with diabetes are unable to achieve glycemic control, presenting a gap in the delivery of self-management education and behavior change. Machine learning and recommender systems, which have been used within the health care setting, could be a feasible application for diabetes management programs to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A prototype application designed to support improved health behaviors in n=50 prediabetic participants shared results supporting a focus on applications that are easy to use and perceived as useful [55]. A much larger study of over 16,000 users of a phone-based app for self-management of T2D reported that app engagement was associated with improved patient outcomes (as measured by blood A1C) [49].…”
Section: Diet Sleep and Physical Activity Four Studies Examined Appli...mentioning
confidence: 80%
“…A prototype application designed to support improved health behaviors in n=50 prediabetic participants shared results supporting a focus on applications that are easy to use and perceived as useful [55]. A much larger study of over 16,000 users of a phone-based app for self-management of T2D reported that app engagement was associated with improved patient outcomes (as measured by blood A1C) [49].…”
Section: Diet Sleep and Physical Activity Four Studies Examined Appli...mentioning
confidence: 80%